STRATEGI ALIANSI DALAM MENGHADAPI GLOBALISASI (STUDY PADA PERUSAHAAN FURNITURE DI KABUPATEN JEPARA) - Apriyanti, Apriyanti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2014)
The problem that is faced by furniture entrepreneur at Jepara is limitation of production capacity and limitation of design that have had. So produce can’t fulfi the buyer demand in at a certain time. This case can be anticipated by make an alliance strategy between several companies, where this solution is main alternative to face the problem. This strategy model was proposed by Michael Yoshino and Rosabeth Kanter where alliance strategy can be happen in various form, which in fact it is a base form marketing alliance that, enclose: product or sevice alliance, promotional alliance, logistic alliance and pricing collaborations. This examination intend to give alternative of formulation strategi that will be used by company in make alliance strategy.To reach the purpose in order to get exact strategy formulation is used by analisis tool that are SWOT Matric, BCG Matric, and QSP Matric. With first base by identifying external factor and internal factors. The result of alliance strategy analysis formulation at furniture company according analysis result of SWOT Matric, BCG Matric, and QSP Matric are recommended 4 strategy that is done by each company with step priority application as follow: I Strategic service alliance, II Strategic opportunity alliance, III Strategic pricing collaboration and IV Strategic promotional alliance.